TANTANGAN MANAJEMEN KELAS GURU SEKOLAH DASAR DI INDONESIA: TINJAUAN SISTEMATIK LITERATUR REVIEW ERA GENERASI ALPHA : - - jamilatun nafiah; Titiek Rohanah Hidayati; Erma Fatmawati (EBTIDA': Jurnal Pendidikan Dasar Islam, 2026)
Classroom management is a crucial activity for teachers to ensure optimal learning. As we enter the digital era, with Generation Alpha students dominating primary education, classroom management faces various challenges that teachers need to address. This study aims to describe and analyse the challenges of classroom management for teachers in the Generation Alpha era. The research method employed a literature review using the PRISMA protocol through the stages of identification, screening, eligibility, and inclusion. The databases consulted were ResearchGate, Sinta, and Google Scholar, with inclusion and exclusion criteria covering publications from 2022 to 2025. The PRISMA selection results identified 45 articles, of which 5 passed the screening and eligibility stages. Findings from these 5 articles indicate that classroom management challenges in primary schools during the Generation Alpha era align with the five domains outlined by Evertson & Weinstein: the physical environment, rules and procedures, student behaviour, instructional management, and teacher-student relationships. These challenges include limited facilities, low teacher pedagogical competence, diverse student characteristics, parental intervention, and curriculum adaptation. Addressing these issues requires comprehensive synergy between teachers, families, and schools. Further research is recommended to conduct empirical studies and explore technology-based strategies using a mixed-methods approach for more comprehensive results. Keywords: The Challenges of Classroom Management, Generation Alpha